THE EFFECT OF SONGS ON PRIMARY SCHOOL STUDENTS' MOTIVATION - Sabriye Sener; Didem Erkan (Informascope, 2018)
In language classes songs have been used for many years. Many studies have pointed out that students can take advantage of music in classes in terms of learning grammar, pronunciation and vocabulary. This study aims to explore the role of using songs on students' motivation in primary level. The dominant/sequential design of the mixed methods approach was applied to the study. The quantitative data were elicited with a quasi-experimental design and qualitative data were collected by means of observations. The data were collected from the students of a state elementary school in a rural area of Denizli province during the winter semester of 2017-2018 education year. The participants were 25 5th graders; 17 girls and 8 boys.  Descriptive analyses were used in order to form the frequencies and percentages of the quantitative data. For the observation data, a matrix was created in Microsoft Word to calculate the average scores of three dimensions of motivation, participation, interest and attention. The perceptions of the observers were elicited and analyzed by means of content analysis. The results of the research showed that the students were more motivated and eager to participate into the activities when songs were used in their classes. The perceptions of the students and teachers were similar. Keywords: Motivation, songs, young learners, interest, learning English